Best wishes - Mlynowski, Sarah; Vee, Maxine (New York, NY : Scholastic Inc., 2023)
After her best friend ditches her, fifth-grader Becca, feeling devastated and alone, yearns for people to like her, so when a magical bracelet grants her wish to have loads of friends, she soon discovers having a dream come true is not as simple as it seems.
Keywords: Wishes -- Juvenile fiction; Magic -- Juvenile fiction; Friendship -- Juvenile fiction; Schools -- Juvenile fiction; Diaries -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; Fantasy fiction; Humorous fiction